De geweerfabriek van Petrus Regout (1842-1843): een kortstondig avontuur - de Beaumont, Eddy (Studies over de sociaaleconomische geschiedenis van Limburg, 2022)
Around 1840, percussion muskets became more and more common in European armies. To keep up with this development, under great time and financial pressure, the Dutch Department of War awarded a contract to convert its muskets to a contractor who was unfamiliar with the arms industry: the Maastricht entrepreneur Petrus Regout. Regout, who accepted an extreme low price, seriously underestimated the scope of the transformation. Due to bad management his ‘musket company’ soon headed towards bankruptcy. He was forced to give back the contract. In his arrogance Regout ignored the advice of representatives of the Dutch artillery who supervised the process. It was a missed opportunity for a dynamic entrepreneur as Regout. The article highlights a rather neglected episode of his business career.